2017
DOI: 10.1155/2017/2548957
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Functionalized MOFs Incorporated Mixed Matrix Hollow Fiber Membrane for Gas Separation

Abstract: The metal-organic framework (MOFs) of MIL-53 was functionalized by aminosilane grafting and then incorporated into Ultem®1000 polymer matrix to fabricate mixed matrix hollow fiber membrane (MMHFM) with high separation performance. SEM, XRD, and TGA were performed to characterize the functionalized MIL-53 and prepared MMHFM. The filler particles were embedded in membrane successfully and dispersed well in the polymer matrix. The incorporation of MOFs endowed MMHFM better thermal stability. Moreover, effects of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 39 publications
(46 reference statements)
0
6
0
Order By: Relevance
“…Referring to Table 3, the CO 2 permeability and CO 2 /CH 4 selectivity increase while CH 4 permeability decrease for all the resultant mixed matrix membranes compared to pure 6FDA-durene membrane. This could be due to the introduction of amine-functionalized ZIF-8 fillers which increased the inter-segmental spacing between polymer chain near the fillers [33,63]. In addition, it can be observed that the values of µ CO 2 are positive as shown in Table 3, which agree that the incorporation of amine-functionalized ZIF-8 filler enhanced the gas permeability [24].…”
Section: Gas Permeation Resultsmentioning
confidence: 52%
“…Referring to Table 3, the CO 2 permeability and CO 2 /CH 4 selectivity increase while CH 4 permeability decrease for all the resultant mixed matrix membranes compared to pure 6FDA-durene membrane. This could be due to the introduction of amine-functionalized ZIF-8 fillers which increased the inter-segmental spacing between polymer chain near the fillers [33,63]. In addition, it can be observed that the values of µ CO 2 are positive as shown in Table 3, which agree that the incorporation of amine-functionalized ZIF-8 filler enhanced the gas permeability [24].…”
Section: Gas Permeation Resultsmentioning
confidence: 52%
“…To overcome these limitations and increase the performance of polymer membranes, inorganic materials are integrated into polymer matrix to form mixed matrix membranes (MMMs). Over the years, several types of conventional inorganic fillers were used in the development of mixed matrix membrane such as zeolites [ 3 ], carbon molecular sieve (CMS) [ 11 ], activated carbon [ 12 ], metal-organic frameworks [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ], carbon nanotubes (CNTs) [ 22 ], metal oxides, mesoporous materials, non-porous material, and lamellar inorganic materials [ 23 ]. Common types of MMMs contains two phases which are the polymer (continuous) phase and a dispersed inorganic phase [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Metal-organic frameworks (MOFs) are a satisfactory alternative to improve the permeation properties of membranes because of its large surface area, high porosity, adsorption capacity, and good compatibility [ 15 ]. This has led to the utilization of MOFs in numerous applications which include gas/liquid separation, catalysts, medicine, and electronics [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Membrane separation technology is widely used for the removal of CO 2 compared to conventional typical technologies it offers advantages such as smaller foot print and less energy consumption [7]. Among the various membrane materials, mixed matrix membranes (MMMs) are widely reported for CO 2 separation because of their superior characteristics such as low cost and higher separation performance [8].…”
Section: Introductionmentioning
confidence: 99%